(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
To ensure reliable and accurate flexible satellite operations, it is crucial to develop effective control schemes. This paper proposes an interesting PD controller and observer scheme for a flexible satellite. Specifically, a functional observer aimed to detect and mitigate actuator fault occurrences, complemented by an output feedback-based control system to effectively compensate for the satellite disturbances and vibrations. The controller achieves enhanced steady-state tracking accuracy by handling the satellite’s flexible dynamics as disturbances. The convergence of tracking error and stability of the closed-loop system is ensured through Lyapunov analysis. The performance of the proposed control scheme is demonstrated numerically, which revealed significant improvements in satellite attitude control precision and stability against vibration issues with actuator faults.